Low level of plasma VEGF-A and C allele of -2578*C/A polymorphism in the VEGF-A gene are risk factors of diabetic foot ulcer in Javanese ethnic - Rahayu, Ika; Sinorita, Hemi; Timotius, Kris Herawan; Sadewa, Ahmad Hamim (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2021)
Diabetes mellitus (DM) is caused by abnormal insulin secretion, impairedinsulin action, or both. Approximately 12-25% of type 2 diabetes mellitus(T2DM) patients will develop diabetic foot ulcers (DFU). Vascular endothelialgrowth factor (VEGF) is a group of platelet-derived growth factors (PDGF)which have a potential role in angiogenesis. Low levels of VEGF-A can causeinsufficient angiogenesis leading to wound healing inhibition. The 2578*C/Apolymorphism of VEGF-A gene has been reported as a candidate markerfor the DFU development. However, the variant role in the development ofDFU in Javanese ethnic needs to be clarified. This study was conducted tocompare VEGF-A levels and the -2578*C/A polymorphism of the VEGF geneamong diabetic patients with and without DFU in Javanese ethnic. In thiscase-control study, the T2DM individuals with DFU as case group (n=19) andwithout DFU as control group (n=41) were recruited. The VEGF-A levelsweredetermined by ELISA. The ARMS-PCR technique was applied to investigate thepresence of -2578*C/A polymorphism of the VEGF gene. Data were analyzedwith independent t, Mann-Whitney, Chi-square, and Kruskal-Wallis tests withsignificance level of p<0.05. The median of plasma VEGF-A level was significantlydifferent between case and control groups (p=0.001). The genotype frequencyof -2578*C/A polymorphism of VEGF gene was no difference between case andcontrol groups. However, individuals with C allele have a higher risk factor todevelop DFU than A allele (CC+CA vs AA;p=0.042; OR=2.5). The plasma VEGF-Alevels were lower in T2DM subjects with DFU than those without DFU. Inconclusion,individuals with C allele of -2578*C/A polymorphism of VEGF geneare more susceptible to have DFU than individuals with A allele in Javaneseethnic with T2DM.